Examining The Challenges of Using Google Class in Teaching Geography in Secondary Schools of Kabale Municipality. - Amanya, Godfrey (Kabale University, 2024)
The major purpose of this research was to identify the challenges of using Google class in teaching geography in secondary schools of Kabale municipality.